Self-Correction vs. Lecturer-Correction: Effects on Research Achievement and Alcohol Use in Intellectual Disabled Undergraduates in Federal Universities of Southern Nigeria (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Aim: Within Nigerian universities, students with intellectual disabilities remain under-supported in terms of personalized instructional strategies that target both academic improvement and psychosocial well-being. The purpose of the study was to compare self-correction vs Lecturer-correction: Effects on research achievement and Alcohol use in Intellectual Disabled undergraduates in Federal Universities of Southern Nigeria. Method: This study adopted a quasi-experimental research design. The area of the study is Southern Nigeria. The population consists of all 3,092 students with intellectual disabilities enrolled in two selected federal universities in Southern Nigeria, specifically in Cross River and Akwa Ibom States. The sample size for this study was 120 final-year students with intellectual disabilities who depend on alcohol to cope with stress and improve self-esteem using a multi-stage sampling technique. Three instruments were used for data collection. They were the Research Achievement Test (RAT), the Interest Inventory Test (IIT), and the Alcohol Use Screening Tool (modified AUDIT). The screening criteria for alcohol dependence are that students must be 18 years and older, students must have a history of substance use, mental health conditions (depression, anxiety), and a history of use of medications contraindicated with alcohol. The study was validated by Psychology, Measurement, and Evaluation experts at the University of Calabar. The data collected were analyzed for internal consistency using the Cronbach Alpha method, which yielded a reliability index of 0.83. The test scores for the study were generated from pre-tests and post-tests using the Research Methods Achievement Test and Research Method Interest Inventory Test.Mean and standard deviation were used to answer the research questions. The pretest-posttest mean gains of each strategy of the two strategies were computed. Also, the null hypotheses formulated for the study were tested at a 0.05 level of significance using Analysis of Covariance (ANCOVA).Results: The findings revealed that student correction strategies are more effective than lecturer correction strategies in enhancing the research method achievement of students with intellectual disabilities. The self-correction strategy significantly improves student interest in research methods more than the lecturer-led correction approach. There is a significant difference in achievement between male and female students, regardless of the correction strategy used. No statistically significant difference in interest scores between male and female students taught research methods using either lecturer-correction or self-correction strategies. Male and female students differed in their alcohol use outcomes following instruction using either the self-correction or lecturers’ correction strategies.Conclusion: Based on the result of the study, it was concluded that student correction strategies are more effective than lecturer correction strategies in enhancing the research method achievement of students with intellectual disabilities. The self-correction strategy significantly improves student interest in research methods more than the lecturer-led correction approach. There is a significant difference in achievement between male and female students, regardless of the correction strategy used. No statistically significant difference in interest scores between male and female students taught research methods using either lecturer-correction or self-correction strategies. Male and female students differed in their alcohol use outcomes following instruction using either the self-correction or lecturers’ correction strategies.Recommendation: Given the superior effectiveness of student correction strategies over lecturer-led corrections in enhancing students’ achievement in research methods, it is recommended that educators integrate structured self-correction approaches into their teaching. This can be achieved through guided reflection exercises, peer review tasks, and the use of checklists or correction templates that promote independent learning and metacognitive development.